Flaps in the management of open tibial fractures - Karikalan, T. (International Journal of Research in Orthopaedics, 2019)
Background: The prognosis in open fractures is primarily determined by the amount of soft tissue loss and the level of contamination. Severe open tibial fractures usually require combined orthoplastic approach in the management. Our aim is to study the effectiveness of soft tissue flaps in the management of type III B open tibial fractures. Methods: The study material consists of 20 cases of grade III B open tibial fractures admitted in our institution. Under anaesthesia, wound debridement was done and fracture stabilised with external fixator or IM nail depending upon the wound status. Patient underwent flap cover once the wound was fit. Periodic follow up was done. Results: Nonunion occurred in one patient (5%). Chronic osteomyelitis developed in two patients (10%). Deep infection occurred in three cases (15%). There was no secondary amputation in our series. The average union time of fracture was 30.1 weeks. Lower third fractures and those patients with extensive soft tissue injury, delayed flap cover and flap failure had longer union time. Conclusions: Fasciocutaneous flap has definitive role in the management of type III B open tibial fractures with soft tissue loss.